The Relationship Between Organizational Ethics And Workplace Inclusion On Employee Commitment - Risma Indriyani; Arya Budi Sutopo; Rina Yuliastuti; Agas Adli; Istifah Mahayuwati; Daffa Fauzan Nugroho (Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the relationship between organizational ethics and workplace inclusion on employee commitment. Strong organizational ethics reflect the values of fairness, integrity, and moral responsibility that are consistently implemented in the workplace, while workplace inclusion emphasizes recognition, acceptance, and equal opportunities for all employees without discrimination. Employee commitment is a crucial factor influencing performance, loyalty, and organizational sustainability. This study employs a quantitative approach using a survey method involving employees from various organizational sectors. The data were analyzed using regression analysis to test the effects of organizational ethics and workplace inclusion on employee commitment. The results indicate that organizational ethics and workplace inclusion have a positive and significant relationship with employee commitment. These findings suggest that organizations that uphold ethical principles and implement inclusive practices tend to achieve higher levels of employee commitment. Therefore, strengthening organizational ethics and workplace inclusion is an essential strategy to enhance employee commitment and organizational sustainability.